Verdrängen Ein-Euro-Jobs sozialversicherungspflichtige Beschäftigung in den Betrieben? - Christian Hohendanner (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2007)
Using a fixed-effects panel-estimation of the years 2004 and 2005 of the IAB Establishment Panel, this article tries to answer the following question: Do the so-called One-Euro-Jobs have an effect on the growth rate of regular employment, covered by the social security system? The analysis finds a negative effect in Eastern Germany. In Western Germany a corresponding effect is not identified.
Keywords: C23; I38; J08; L30; M50; 330; Arbeitsgelegenheit - Auswirkungen; Beschäftigerverhalten; sozialversicherungspflichtige Arbeitnehmer; IAB-Betriebspanel; Substitutionseffekte; Personalplanung; Beschäftigungseffekte; befristeter Arbeitsvertrag; Ostdeutschland; Westdeutschland; Bundesrepublik Deutschland; Arbeitsbeschaffung; Lohnsubvention; Beschäftigungseffekt; Arbeitsverhältnis; Deutschland